Insights on the effects of the hydrothermal alteration in the El Laco magnetite deposit (Chile) - Velasco, Francisco; Tornos Arroyo, Fernando (Sociedad Española de Mineralogía, 2020)
Congreso SEM-SEA 2012, reunión conjunta de las sociedades españolas de Mineralogía (XXXII Reunión) y Arcillas (XXII Reunión), celebrado en Bilbao entre el 27 y 30 de Junio de 2012 The understanding of the origin of the recent (ca. 2 Ma) El Laco deposit (Fig. 1), with near 1 Gt of almost pure magnetite/hematite, is considered critical for the interpretation of the Kiruna type magnetite-apatite style of mineralization, an end-member of the IOCG group of deposits. Despite the abundant studies conducted in the last decades on El Laco, with little erosion, well preserved volcanic features and excellent conditions of exposure, there is no agreement between models that support a genesis related to the hydrothermal replacement of preexisting andesitic rocks (Rhodes & Oreskes, 1999; Rhodes et al., 1999) and those which interpret the deposit as magmatic flows and dikes product of the crystallization of an iron oxide melt (Frutos & Oyarzun, 1975; Nyström & Henríquez, 1994; Naslund et al., 2002; Henríquez et al., 2003; Tornos et al., 2011). To solve this fascinating controversy is crucial to understand the problem from a global point of view, integrating geological and geochemical data of the magmatic and hydrothermal rocks present in the area Departamento de Mineralogía y Petrología, Universidad del País Vasco, España Instituto Geológico y Minero de España, España Departamento de Educación, Universidades e Investigación, Gobierno Vasco, España